Review of Prediabetes and Hypertensive Disorders of Pregnancy - Carris, Nicholas W.; Nwabuobi, Chinedu K.; He, Weiwei; Bullers, Krystal; Wilson, Roneé E.; Louis, Judette M.; Magness, Ronald R. (American Journal of Perinatology, 2019)
Obesity and diabetes increase hypertensive disorders of pregnancy (HDP) risk, thus preventive interventions are heavily studied. How pregestational prediabetes and related interventions impact HDP risk is less characterized. Therefore, we searched and reviewed the literature to assess the impact on HDP risk of prediabetes and varied interventions. We identified 297 citations related to pregnancy, prediabetes, and early pregnancy interventions. We also reviewed the references and citations of included articles. We included five studies assessing HDP outcomes in women with first trimester hemoglobin A1c in the prediabetes range (5.7–6.4%). One prospective observational study demonstrated first trimester hemoglobin A1c (5.9–6.4%) is associated with increased HDP risk, while another prospective observational study and one retrospective observational study had similar trends without statistical significance. A small and underpowered randomized controlled trial demonstrated initiating gestational diabetes mellitus treatment (i.e., diet, monitoring, ± insulin) in response to first trimester hemoglobin A1c (5.7–6.4%) did not statistically reduce HDP compared with standard care. One retrospective observational study suggested metformin, when started early, may reduce HDP risk in patients with prediabetes. Pregestational prediabetes appears to increase HDP risk. Interventions (i.e., metformin, diet/glucose monitoring, and/or exercise) to reduce HDP risk require additional study with long-term follow-up.
Keywords: first trimester of pregnancy; hemoglobin A1c; hypertension; prediabetes; preeclampsia